Analysing gender and institutional change in academia: evaluating the utility of feminist institutionalist approaches. Issue 6 (1st November 2020) - Clavero, Sara; Galligan, Yvonne
ABSTRACT: This article explores research on gender and institutions for the purposes of informing analytical frameworks for research on institutional change with regard to gender equality in higher education. Drawing on feminist institutionalist studies that explore the relationship between gender, institutions and institutional continuity and change, the aim is to evaluate how this body of scholarship can be adapted to an analysis of the dynamics of gender equality plan implementation in universities.S